Представления о чудесном в избранных жанрах польской и русской народной прозы - Rzepnikowska, Iwona (Slavia Orientalis, 2025)
This paper explores the representations of the miracle and of miraculousness in three distinct genres of Polish and Russian folk prose. This issue has repeatedly attracted the attention of researchers of Slavic folk culture, who usually focus on a set of texts representing a single genre. I believe that a comparative approach, which involves the comparison of narratives belonging to different genre models, is more insightful. In this case, they are a belief story, a tale of magic and a religious tale. The selected material reflects various aspects of beliefs about the miraculous, influenced by different worldview systems and interestingly expressed in each narrative type. Based on the above, it is possible to identify three types of miraculousness, mythological (belief-based), magical and folk-religious.